2023
DOI: 10.1186/s12876-023-02772-w
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: 3-year interim analysis results of the VISION trial to evaluate the long-term safety of vonoprazan as maintenance treatment in patients with erosive oesophagitis

Abstract: Background VISION is a randomised, phase 4, open-label, parallel-group, multicentre study conducted in 33 centres in Japan. The aim of this study was to assess the long-term safety of vonoprazan for maintenance treatment of healed erosive oesophagitis versus lansoprazole. Methods Patients with endoscopically diagnosed erosive oesophagitis were randomised 2:1 to once-daily vonoprazan 20 mg or lansoprazole 30 mg, for a 4- to 8-week healing phase. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…These findings align with those from the VISION trial and suggest that the differing likelihood of BS occurrence between PPIs and vonoprazan could stem from variations in their mechanisms of acid suppression. 17 …”
Section: Discussionmentioning
confidence: 99%
“…These findings align with those from the VISION trial and suggest that the differing likelihood of BS occurrence between PPIs and vonoprazan could stem from variations in their mechanisms of acid suppression. 17 …”
Section: Discussionmentioning
confidence: 99%
“…43 A clinical study evaluating the long-term safety of vonoprazan in the treatment of reflux esophagitis reported no serious adverse events such as gastric mucosal neoplasia after 3 years of vonoprazan maintenance. 44 Carcinoid tumors have been reported after long-term use of PPIs. 45 In addition, night-time acid suppression by tegoprazan and vonoprazan was not dependent on CYP2C19 phenotypes, whereas esomeprazole tended to be influenced by CYP2C19 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the VISION trial 17 highlighted a notable increase in the prevalence rate of HPs from 3.7% to 14.7% over a threeyear period in patients initiating P-CAB treatment. Additionally, Shinozaki et al 18 reported a notably higher prevalence of HP among patients receiving P-CAB for more than one year compared to that of non-P-CAB users.…”
Section: Hyperplastic Polypsmentioning
confidence: 99%
“…The other case report by Nishimura et al 16 discussed the notable decrease and regression of FGPs subsequent to P-CAB discontinuation in a patient with anemia, with a concomitant reduction in serum gastrin levels compared to that before drug discontinuation. Moreover, Haruma et al 17 conducted a multicenter prospective study (VISION trial) and reported a noteworthy increase in the prevalence of FGPs from 43.7% to 66.1% over a three-year period following the initiation of P-CAB therapy. Additionally, Shinozaki et al 18 found a notably higher prevalence of FGPs among patients receiving P-CAB for more than one year compared to that in non-P-CAB users.…”
Section: P-cab-associated Gastric Mucosal Lesionsmentioning
confidence: 99%